INSTAGRAM-MEDIATED PROJECT-BASED LEARNING IN TEACHING SPEAKING SKILL - Agung Ahmad Syahida; Andang Saehu; Hanna Sundari (University of Kuningan, 2022)
This study was grounded in a mixed-method design that aimed to analyze the differences between learning speaking taught using Instagram-mediated project-based learning and those taught using conventional techniques. In addition, this study was also conducted to investigate the challenges faced and explore the strategies given by students in solving problems in the application of Instagram-mediated project-based learning techniques. This study involved 12th-grade students who were randomly selected to be the control and experimental groups. The research instruments used were pre-speaking tests and post-speaking tests to measure the level of students' speaking skills and a questionnaire to investigate the challenges faced and explore the strategies provided by students in Instagram-mediated project-based learning conducted by the experimental group. The significance score was 0.000 smaller than 0.05. This confirmed that the Instagram-mediated project-based learning technique proved to have a significant difference. In qualitative stage of analysis, it was revealed that the challenges the students faced were categorized into language barriers, video making, and external factors. From the results of this study, it can be concluded that the Instagram-mediated project-based learning technique was proven to be effective in improving students' speaking skills. Therefore, school policymakers can provide a wider internet network to support this learning technique. However, the results of this study recommended similar research on speaking skills in other materials in more depth with a wider scope.Keywords: Instagram; project-based learning; MALL; speaking; mixed-method.